Zonificación de Periodos Fundamentales del Suelo, mediante Vibraciones Ambientales, de la Zona Centro Oeste del Límite Urbano de la ciudad, cantón y provincia de Loja. - Bueno Apolo, Jomahira Elizabeth (2024)
The engineering study that refers to a seismic evaluation in an urban area requires detailed studies, regarding geological, geotechnical and seismological aspects, which help to identify the different risks and vulnerabilities that arise. The present work contributes to the study of the seismic behavior of soils by determining the predominant and dominant periods of the soil, evaluated using the H/V spectral ratio of the Nakamura (1989) method, a procedure applied on a 250m x 250m grid, having as results the seismic zoning of the central western part of the Loja basin’s urban limit, where it is classified into the categories of medium range periods (0.2s - 0.8s) and long periods (0.8s - 1.4s), these periods were correlated with the geological conditions of the area, although an irregular distribution is present at different points due to the variety of their powers and materials, their effect can be estimated. In addition, it is preliminarily determined that the study area is classified into a type C and D soil profile. With the information obtained from the periods, it can be used to determine the structure of the subsoil model, obtaining the geotechnical classification for purposes of seismic calculations and to what extent it could affect earthquakes in the urban area, making it possible to predict the damage, which would be of great importance for the design and construction of civil works under the earthquake resistant criterion. The results obtained will be the subject of study for further research. Keywords: Nakamura method, predominant periods, environmental vibrations, spectral ratio, model structures, Loja basin.